THE CONTRIBUTION OF TEACHERS’ PEDAGOGICAL COMPETENCE TOWARD THE EFFECTIVENESS OF TEACHING OF ENGLISH AT MTSN BALANG-BALANG - Julkifli Hidayat Ada; St Azisah (ETERNAL (English, Teaching, Learning and Research Journal), 2016)
This research aims at finding the Contribution of Teachers’ Pedagogical Competence toward the Effectiveness of Teaching of English at MTsN Balang-Balang. This research used the qualitative descriptive research, that is the researcher observe the teaching and learning process and interact with the teacher by interview and observation.The researcher found that the contribution of teachers pedagogy competence toward the effectiveness of teaching of English, seems the teacher have made serious effort in conducting the teaching and learning to make more effective in teaching of English in the class. This contribution seen from how they organize the learning from arranged the teaching plan, teaching and learning process, and assessment. The teachers were also able to motivate the students to attend the class, induce the students to learn the material as well as explain the material clearly so that the students could comprehend it easily. Furthermore, the students were also active in asking and answering questions both from the teacher. In the section of discussion, the students were also able to conclude the materials taught during the teaching and learning process. It means that teacher’s pedagogy competence could improve students’ motivation to learn.